Structure, Raman and luminescence characteristics of Zn1-xHfxO (0≤x≤0.1) nanocrystals prepared via N-(methyl)mercaptoacetamide assisted microwave approach. Issue 15 (15th October 2020) - Mahmoud, Waleed E.
Abstract: A series of Zn1-x Hfx O (0 ≤ x ≤ 0.1) nanocrystals was synthesized via the N-(methyl)mercaptoacetamide assisted microwave approach. The influence of the Hf dopant on the crystal structure, Raman lattice vibrations, and luminescent emission spectra was studied. XRD measurements revealed that the inclusion of the Hf dopant in the Zn cites instigated the expansion of the ZnO lattice while preserving its hexagonal structure. The XRD, SEM and DLS measurements demonstrated that the Hf dopant increased the size of ZnO nanocrystals from 2.5 ± 0.1 nm to 11.5 ± 0.1 nm. The EDS spectra confirmed the stoichiometry of the prepared samples. The zeta potential measurement revealed that the Hf dopant is incorporated within the ZnO nanostructure. The Raman spectra showed that the Hf dopant was efficiently incorporated into the ZnO crystals without altering its internal structure. The UV–vis. spectroscopy indicated that the partial substitution of Zn atoms by Hf atoms leads to modulation of the optical bandgap. Luminescence measurements revealed that the inclusion of the Hf dopant in the Zn cites resulted in suppression of the ZnO crystal defects. The XPS measurements confirmed that the inclusion of Hf dopant in the Zn cites resulted in a reduction of the amount of oxygen vacancy which actes as a trap centers for the photogenerated electrons. Therefore, a modulation of the visible spectra occurred, while the Hf dopant did not affect the intensity of UV-emission band of ZnO nanocrystals. Therefore, the Zn1-x Hfx O (0 ≤ x ≤ 0.1) nanocrystals are favorable as potential candidates for both catalytic and luminescent device applications.